2020
DOI: 10.1029/2019wr026430
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Solute Transport in Heterogeneous Beach Aquifers Subjected to Tides

Abstract: A numerical study, based on a variably saturated groundwater flow model within a Monto Carlo framework, was conducted to investigate flow and solute transport in a heterogeneous beach aquifer subjected to tides. The numerical simulations were conducted based on our previous tracer experiments performed in a laboratory beach. Heterogeneity is assumed to be multifractal generated using the Universal Multifractal model. Our results show that heterogeneity greatly alters temporal and spatial evolution of the trace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 115 publications
1
24
0
Order By: Relevance
“…Numerical simulations of water flow toward the root layer were conducted with randomized heterogeneous fields; a simple linear correlation was assumed between height of the capillary fringe and saturated K. Their results revealed that an increase in heterogeneity at the root-soil interface leads to high root water uptake rates. While a number of previous studies have explored the effects of geologic heterogeneity on flow and transport processes in coastal aquifer systems, the studies only considered spatial variability in K (Geng et al, 2020b;Heiss, Michael, & Koneshloo, 2020;Lu et al, 2013;Michael et al, 2016;Pool et al, 2015;Sebben et al, 2015). In coastal aquifers, due to oceanic forcing (e.g., tides and waves), variably saturated conditions are ubiquitously observed in nearshore beach systems; therefore, it is important to consider heterogeneity of sediment capillarity when investigating coastal flow and transport processes.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations of water flow toward the root layer were conducted with randomized heterogeneous fields; a simple linear correlation was assumed between height of the capillary fringe and saturated K. Their results revealed that an increase in heterogeneity at the root-soil interface leads to high root water uptake rates. While a number of previous studies have explored the effects of geologic heterogeneity on flow and transport processes in coastal aquifer systems, the studies only considered spatial variability in K (Geng et al, 2020b;Heiss, Michael, & Koneshloo, 2020;Lu et al, 2013;Michael et al, 2016;Pool et al, 2015;Sebben et al, 2015). In coastal aquifers, due to oceanic forcing (e.g., tides and waves), variably saturated conditions are ubiquitously observed in nearshore beach systems; therefore, it is important to consider heterogeneity of sediment capillarity when investigating coastal flow and transport processes.…”
Section: Introductionmentioning
confidence: 99%
“…provide an extensive analysis on the impact of geologic heterogeneity on seawater circulation, while Kreyns et al (2020) document that freshwater discharge can extend further offshore in heterogeneous volcanic aquifers when compared to homogeneous counterparts. Geng et al (2020) use simulations to investigate the impact of subsurface heterogeneity on tidally influenced circulation, thereby confirming the importance of coupling heterogeneity with influences on an aquifer's hydrologic dynamics in order to further constrain geologic impacts on solute transport. further detail heterogeneity's influence on variable solute transport and decreased travel time through an aquifer in response to relatively deeper groundwater pumping.…”
Section: Numerical Simulations Of Density-dependent Flow and Heterogeneitymentioning
confidence: 92%
“…For the purpose of this study, the e-folding time serves as a characteristic of the response rate, with the amount of time corresponding to the relative speed of response to a perturbation in recharge. We additionally assess flow topology using the Okubo-manuscript submitted to Water Resources Research Weiss (OW) method to provide a mechanistic explanation for the simulation results (de Barros et al, 2012;Geng et al, 2020). e-folding time in response to inflow perturbations is larger by at least a factor of three for the HSF model when compared to the homogeneous model (Figure 8).…”
Section: Metrics For Assessing Interface Geometry Sensitivity and Stabilitymentioning
confidence: 99%
“…For the purpose of this study, the e-folding time serves as a characteristic of the response rate, with the amount of time corresponding to the relative speed of response to a perturbation in recharge. We additionally assess flow topology using the Okubo-manuscript submitted to Water Resources Research Weiss (OW) method to provide a mechanistic explanation for the simulation results (de Barros et al, 2012;Geng et al, 2020).…”
Section: Metrics For Assessing Interface Geometry Sensitivity and Stabmentioning
confidence: 99%
“…Density-dependent numerical simulations of brine-tofreshwater interfaces in arid basins have either been homogeneous (Vásquez et al, 2013;Tejeda et al, 2003) or simply layered models of local geology that underestimate basin-scale heterogeneity and produce unrealistic results of the modeled interface (Marazuela et al, 2018). Previous geostatistical modeling documented the influence of subsurface heterogeneity on seawater circulation in coastal aquifers Geng et al, 2020;Kreyns et al, 2020).…”
Section: Introductionmentioning
confidence: 99%